Infective endocarditis as a mid-term complication after transcatheter aortic valve implantation: case report and literature review - Sulženko, Jakub; Toušek, Petr; Línková, Hana (Catheterization and cardiovascular interventions, 2014)
Few cases of infective endocarditis (IE) as a complication of percutaneous transcatheter aortic valve implantation (TAVI) have been reported. Here, we present a case of IE caused by Streptococcus viridans that occurred 6 months after TAVI with the corevalve revalving system. The patient was successfully treated with antibiotics and was asymptomatic during the 2 years after IE. We also present a review of the literature, including 15 published cases of IE after TAVI.
Keywords: Aortic Valve Stenosis; Prosthesis Design; Heart Valve Prosthesis Implantation; streptokokové infekce; protézy - design; výsledek terapie; aortální stenóza; Tomography, X-Ray Computed; Cardiac Catheterization; Viridans Streptococci; infekce spojené s protézou; srdeční chlopně umělé; chirurgická náhrada chlopně; Time Factors; časové faktory; lidé; Heart Valve Prosthesis; Anti-Bacterial Agents; Prosthesis-Related Infections; viridující streptokoky; Treatment Outcome; Aged, 80 and over; Humans; Male; Streptococcal Infections; bakteriální endokarditida; srdeční katetrizace; echokardiografie transezofageální; Echocardiography, Transesophageal; senioři nad 80 let; mužské pohlaví; antibakteriální látky; Endocarditis, Bacterial; počítačová rentgenová tomografie